Optimizing the Implementation of Computer-Based Exams to Paperless in the Department of Chemistry of Musamus University - Jesi Jecsen Pongkendek,; Marantika Lia Kristyasari,; Henie Poerwandar Asmaningrum, (Technium Social Sciences Journal, 2023)
This research is a descriptive study that aims to optimize the implementation of computer-based exams in minimizing the use of paper in the Department of Chemistry of Musamus University. The subject of this research is the fifth semester students of the Chemistry Education Department in the Classroom Action Research Course. The research data was obtained through a student response questionnaire with the implementation of a computer-based exam filled in via the Google form. From the results of descriptive data analysis it was obtained that the response of students to the implementation of computer-based exams was positive with an average value of student responses of 83.08%. The conclusion that can be obtained from this research is that the computer-based test with the wondershare quiz creator software can minimize the use of paper. In addition, computer-based exams can make students independent in working on problems, as well as accelerated acceptance of student exam results.